An α-l-Arabinofuranosidase from Trichoderma reesei Containing a Noncatalytic Xylan-Binding Domain - Nogawa, Masahiro (American Society for Microbiology, 1999)
l-Sorbose, an excellent cellulase and xylanase inducer from Trichoderma reesei PC-3-7, also induced α-l-arabinofuranosidase (α-AF) activity. An α-AF induced by l-sorbose was purified to homogeneity, and its molecular mass was revealed to be 35 kDa (AF35), which was not consistent with that of the previously reported α-AF. Another species, with a molecular mass of 53 kDa (AF53), which is identical to that of the reported α-AF, was obtained by a different purification procedure. Acid treatment of the ammonium sulfate-precipitated fraction at pH 3.0 in the purification steps or pepsin treatment of the purified AF53 reduced the molecular mass to 35 kDa. Both purified enzymes have the same enzymological properties, such as pH and temperature effects on activity and kinetic parameters for p-nitrophenyl-α-l-arabinofuranoside (pNPA). Moreover, the N-terminal amino acid sequences of these enzymes were identical with that of the reported α-AF. Therefore, it is obvious that AF35 results from the proteolytic cleavage of the C-terminal region of AF53. Although AF35 and AF53 showed the same catalytic constant with pNPA, the former showed drastically reduced specific activity against oat spelt xylan compared to the latter. Furthermore, AF53 was bound to xylan rather than to crystalline cellulose (Avicel), but AF35 could not be bound to any of the glycans. These results suggest that AF53 is a modular glycanase, which consists of an N-terminal catalytic domain and a C-terminal noncatalytic xylan-binding domain.